Evidence suggesting that the odortypes of pregnant women are a compound of maternal and fetal odortypes. - Beauchamp, G K (1995)
Odortypes--namely, body odors that distinguish one individual from another on the basis of genetic polymorphism at the major histocompatibility complex and other loci--are a fundamental element in the social life and reproductive behavior of the mouse, including familial imprinting, mate choice, and control of early pregnancy. Odortypes are strongly represented in urine. During mouse pregnancy, an outcrossed mother's urine acquires fetal major histocompatibility complex odortypes of paternal origin, an observation that we took as the focus of a search for odortypes in humans, using a fully automated computer-programmed olfactometer in which trained rats are known to distinguish precisely the odortypes of another species. Five women provided urine samples before and after birth, which in each case appropriately trained rats were found to distinguish in the olfactometer. Whether this olfactory distinction of mothers' urine before and after birth reflects in part the odortype and hence genotype of the fetus, and not just the state of pregnancy per se, was tested in a second study in which each mother's postpartum urine was mixed either with urine from her own infant or with urine of a different, same-aged infant. Responses of trained rats were more positive with respect to the former (congruous) mixtures than to the latter (incongruous) mixtures, implying that, as in the mouse, human fetal odortypes of paternal genomic origin are represented in the odortype of the mother, doubtless by circulatory transfer of the pertinent odorants.